DISPOSITIONAL EMPATHY AND CREATIVE PERSONALITY TRAITS OF VISUAL ARTS STUDENTS - Balundė, Audra; Grakauskaitė-Karkockienė, Daiva (Acta Paedagogica Vilnensia, 2015)
The aim of this research was to establish the linkage of a creative personality of students of visual arts and cognitive and emotional empathy and whether the assessment of empathy is related to the gender. 1st–4th year students of two art profile higher schools participated in the research, their age was 18–32 years. The traits of a creative personality were evaluated in accordance with the “Questionnaire on assessment of characteristics of a creative personality” (Туник E. E., 2003). The cognitive and emotional aspects of empathy were evaluated on the basis of the “Interpersonal reactivity index” questionnaire (Davis M. H., 1983). The instrument consists of four seven-item subscales: the perspective-taking scale, contains items which assess spontaneous attempts to adopt the perspectives of other people. Items on the fantasy scale measure the tendency to identify with characters from movies, novels, plays and other fictional situations. The empathic concern scale inquires about respondents‘ feelings of warmth, compassion, and concern for others, while the personal distress scale measures the personal feelings of anxiety and discomfort which result from observing another‘s negative experience. It has been revealed that with the decrease of the assessment of predisposition to risk, personal distress assessment increases. Also, it has been established that with the decrease of complexity assessment, personal distress assessment decreases. With the increase of imagination assessment, fantasy assessment also increases. The assessment of creativity did not differ among males and females; however, the assessment of personal distress in females was higher. Perspective taking and fantasy assessments did not differ among males and females.